Emotional Intelligence, Work-Life Balance, and Work-Related Well-Being: A Proposed Mediation Model - Mahima Nanda (Colombo Business Journal, 2020)
The present study aims to review the existing literature relating to Emotional Intelligence (EI), Work-Life Balance (WLB), and work-related well-being in order to build a model depicting relationships between these variables. For this, various theoretical and empirical studies, which specifically addressed these variables, were examined to build arguments and propositions. These arguments lead us to propose that EI is a vital construct that impacts WLB and various dimensions of work-related well-being, which are, job satisfaction, work engagement and job stress. Further, it suggests that WLB mediates the relationship between EI and work-related well-being. Thus, the paper presents a mediation model depicting linkages between these three variables. It builds an integrative model which will help theorists and researchers to extend literature on work-related well-being and will assist organisations in designing their human resource policies and practices.